Effects of the Antimicrobial Peptide LL-37 and Innate Effector Mechanisms in Colistin-Resistant Klebsiella pneumoniae With mgrB Insertions - Al-Farsi, Hissa M.; Al-Adwani, Salma; Ahmed, Sultan; Vogt, Carmen; Ambikan, Anoop T.; Leber, Anna; Al-Jardani, Amina; Al-Azri, Saleh; Al-Muharmi, Zakariya; Toprak, Muhammet S.; Giske, Christian G.; Bergman, Peter (Frontiers in Microbiology, 2019)
Background: Colistin is a polypeptide antibiotic drug that targets lipopolysaccharides in the outer membrane of Gram-negative bacteria. Inactivation of the mgrB-gene is a common mechanism behind colistin-resistance in Klebsiella pneumoniae (Kpn). Since colistin is a cyclic polypeptide, it may exhibit cross-resistance with the antimicrobial peptide LL-37, and with other innate effector mechanisms, but previous results are inconclusive. Objective: To study potential cross-resistance between colistin and LL-37, as well as with other innate effector mechanisms, and to compare virulence of colistin-resistant and susceptible Kpn strains. Materials/methods: Carbapenemase-producing Kpn from Oman (n=17) were subjected to antimicrobial susceptibility testing and whole genome sequencing. Susceptibility to colistin and LL-37 was studied. The surface charge was determined by zeta-potential measurements and the morphology of treated bacteria was analysed with electron microscopy. Bacterial survival was assessed in human whole blood and serum, as well as in a zebrafish infection-model. Results: Genome-analysis revealed insertion-sequences in the mgrB gene, as a cause of colistin resistance in 8/17 isolates. Colistin-resistant (Col-R) isolates were found to be more resistant to LL-37 compared to colistin-susceptible (Col-S) isolates, but only at concentrations ≥ 50 µg/ml. There was no significant difference in surface charge between the isolates. The morphological changes were similar in both Col-R and Col-S isolates after exposure to LL-37. Finally, no survival difference between the Col-R and Col-S isolates was observed in whole blood or serum, or in zebrafish embryos. Conclusions: Cross-resistance between colistin and LL-37 was observed at elevated concentrations of LL-37. However, Col-R and Col-S isolates exhibited similar survival in serum and whole blood, and in a zebrafish infection-model, suggesting that cross-resistance most likely play a limited role during physiological conditions. However, it cannot be ruled out that the observed cross-resistance could be relevant in conditions where LL-37 levels reach high concentrations, such as during infection or inflammation.